DESIGNING OF OPEN CHANNELS AND CLOSED CHANNELS FOR DRAINAGE FACILITIES IN AIRSIDE - Ajeng Teralina Listya Avandha; Shabrina Ramadhani (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2023)
Drainage facilities are one part of the airside facilities that are important to ensure the safety of the airside area when weather changes occur. This study aims to make drainage that can be carried out to ensure the safety of the airside area from stagnant water. The calculation of airside drainage refers to the planned drainage calculation rules so that the drainage channels can design accordingly so as not to interfere with the operation of other facilities. In the design of drainage work, the material requirements for making open and closed channels at Dewadaru Karimun Jawa Airport must be precisely designed so that the work takes place by the specified planning and quality standards. The research uses a mixed methodology that the exploratory study by conducting a literature study that compares observation. The analysis starts by finding the volume for each work item based on Standar Nasional Indonesia (SNI) 2052-2017, a national iron and concrete standard. The result shows the excavation of soil for making channels, the total volume required is 880.24 m3, the importance of sand is 40.76 m3, the book of substantial rebates of a mixture ratio of 1: 2: 3 is 23.82 m3, and the book of K300 Concrete works for U-Ditch type C channels (100 x 100) is 116.29 m3. For the needs of the required iron volume of 16,415.09 kg, formwork of 1,408.45 m2, stone river masonry size 100 x 100 by 139 m3, stone river masonry size 50x50 amounted to 42.05 m3, and the volume of plastering work of the channel amounted to 192.46 m2. The conclusion of this study is the accuracy of design required to calculate each work item's volume.